The Relationship of Physical Activity with Musculoskeletal Disorders Complaints in Students of the Faculty of Sports Sciences and Public Health - Lastri Silalahi; Richard Palilingan; Agusteive Telew (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Background: Musculoskeletal Disorders (MSDs) are disorders that occur in the muscle, nerve, tendon and joint systems that are generally caused by repetitive physical activity, unergonomic working postures, and excessive workload. Musculoskeletal Disorders (MSDs) in college students is one of the main causes of disability in the world. Students are at risk of developing MSDs due to low physical activity and unergonomic posture. Objective: To determine the relationship between physical activity and complaints of Musculoskeletal disorders (MSDs) in students of the Faculty of Sports Sciences and Public Health. Methods: This study used an analytical quantitative design with a cross sectional approach. The sample of 83 respondents used the purposive sampling technique. The instruments used were the Baecke questionnaire and the Nordic Body Map. Data analysis using the Spearman Rank test. Results: Most respondents had low physical activity (75.9%) and high MSDs complaints (45.8%). The test results showed a significant relationship between physical activity and MSDs (p = 0.002; r = 0.332). Conclusion: There is a significant relationship between physical activity and complaints of musculoskeletal disorders (MSDs) in students of the Faculty of Sports Sciences and Public Health (FIKKM).